Matematika Dalam Al-Qur'an: Belajar Sambil Tafakkur? - M. Imamuddin (KOLONI, 2026)
This study aims to explore and uncover hidden mathematical patterns and phenomena in the structure of the Qur'ān, which have often only been understood from the spiritual and legal dimensions. Using a qualitative approach and textual analysis of the Qur'ān, the researcher analyzed the word order, frequency of occurrence, and relationships between verses. The analysis was carried out on the balance of the words "world" and "hereafter", the proportion of "sea" and "land", and the phenomenon of the number 19. As a result, the research identified various numerical harmonies and proportions, which not only confirm the uniqueness of the Qur'ān as a linguistic miracle, but also as a source of inspiration for scientific and mathematical thinking. Furthermore, the findings emphasize the importance of the concept of "tafakkur" as a bridge connecting faith with rationality, encouraging readers from various backgrounds of academics, students, scholars, and the general public to appreciate the scientific dimensions of the Qur'ān in order to deepen faith and spark continued intellectual exploration.